Remedial effect of cognitive reframing and self-acceptance therapy on enhancement of optimism among students diagnosed with learned helplessness in Ibadan metropolis (2017)
Evidence suggests that learned helplessness impairs learning and contributes to poor academic performance. Regrettably, there is limited empirical literature on intervention to enhance optimism in this population. Therefore, this study examined the effectiveness of Cognitive Reframing (CR) and Self-Acceptance Therapy (SAT) on enhancing optimism among junior secondary school students in Ibadan, Oyo state. Pre-test-post-test control group, quasi experiment design with 3x2x2 factorial matrix was adopted. One hundred and fourteen diagnosed learned helplessness students (Male= 57; Female=57) with age range of 10 to 13 years were purposively drawn from three public secondary schools. The schools were randomly assigned to therapy conditions. Experimental groups were exposed to 10 sessions of therapies. Narvaez Positivity Scale (α =0.73) Quinless and Nelson Learned Helplessness Scale (α=0.77) were utilised for data collection. Results showed that there was a significant main effect of treatment [F (2,101) =13.61; p=0.000<.05, n2=0.21]. Participants treated with CR had superior mean gain (x=59.94) over SAT (X=51.54) and Control Group (X=46.65). There was interactive effect of treatment, gender and age on optimism of secondary school students (F (2,101) = 6.95, p=0.015< 0.05, ƞ2=0.53).This evidence suggests that optimism is amenable to treatment. The researchers recommended the use of the therapies for the remediation of learned helplessness in school settings.